Shikonin Increases Glucose Uptake in Skeletal Muscle Cells and Improves Plasma Glucose Levels in Diabetic Goto-Kakizaki Rats - Öberg, Anette I.; Yassin, Kamal; Csikasz, Robert I.; Dehvari, Nodi; Shabalina, Irina G.; Hutchinson, Dana S.; Wilcke, Mona; Östenson, Claes-Göran; Bengtsson, Tore (PLOS ONE, 2011)
Background There is considerable interest in identifying compounds that can improve glucose homeostasis. Skeletal muscle, due to its large mass, is the principal organ for glucose disposal in the body and we have investigated here if shikonin, a naphthoquinone derived from the Chinese plant Lithospermum erythrorhizon, increases glucose uptake in skeletal muscle cells. Methodology/Principal Findings Shikonin increases glucose uptake in L6 skeletal muscle myotubes, but does not phosphorylate Akt, indicating that in skeletal muscle cells its effect is medaited via a pathway distinct from that used for insulin-stimulated uptake. Furthermore we find no evidence for the involvement of AMP-activated protein kinase in shikonin induced glucose uptake. Shikonin increases the intracellular levels of calcium in these cells and this increase is necessary for shikonin-mediated glucose uptake. Furthermore, we found that shikonin stimulated the translocation of GLUT4 from intracellular vesicles to the cell surface in L6 myoblasts. The beneficial effect of shikonin on glucose uptake was investigated in vivo by measuring plasma glucose levels and insulin sensitivity in spontaneously diabetic Goto-Kakizaki rats. Treatment with shikonin (10 mg/kg intraperitoneally) once daily for 4 days significantly decreased plasma glucose levels. In an insulin sensitivity test (s.c. injection of 0.5 U/kg insulin), plasma glucose levels were significantly lower in the shikonin-treated rats. In conclusion, shikonin increases glucose uptake in muscle cells via an insulin-independent pathway dependent on calcium. Conclusions/Significance Shikonin increases glucose uptake in skeletal muscle cells via an insulin-independent pathway dependent on calcium. The beneficial effects of shikonin on glucose metabolism, both in vitro and in vivo, show that the compound possesses properties that make it of considerable interest for developing novel treatment of type 2 diabetes.